The Case for Media Literacy Implementation in the Social Studies Curriculum (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2022)
Media literacy is a subject that is worthwhile for implementation in social studies classrooms for students in the internet-age. Because of the wealth of information available at any given time, there is a serious need for the education of students on how to find reputable information throughout all the messaging that is spread throughout the media environment. It is now more difficult than ever to procure media information that is not laden with bias, so students need to be informed on how to consume and create media responsibly. Students must be given structure in how they can effectively sift through information that they both consume and propagate as creators, especially in the realm of social media.
Keywords: Media; Literacy; Misinformation; Reasoning; Producers